2003
DOI: 10.1002/jbm.a.20061
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and nanomechanical properties of cementum dentin junction

Abstract: The attachment between cementum and dentin has been given several definitions and nomenclature, including: interzonal layer, intermediate cementum, collagen hiatus, Hopewell-Smith's hyaline layer, and more commonly, cementum-dentin junction (CDJ). Understanding the attachment of two structurally dissimilar hard tissues such as cementum and dentin defined by a junction may provide information necessary to engineer functionally graded materials that can be used for efficient tooth restorations in clinical dentis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 17 publications
3
59
0
Order By: Relevance
“…Collagen fibers are continuous from cementum through the CDJ to root mantle dentin-The AFM micrograph shown in Figure 1e illustrates continuous collagen fibers from the root surface through the CDJ into mantle dentin. Notice the previously reported [8] valley-like CDJ under dry conditions (Fig. 1e).…”
Section: Collagen Fibers Are Continuous From Root Surface Through supporting
confidence: 68%
See 3 more Smart Citations
“…Collagen fibers are continuous from cementum through the CDJ to root mantle dentin-The AFM micrograph shown in Figure 1e illustrates continuous collagen fibers from the root surface through the CDJ into mantle dentin. Notice the previously reported [8] valley-like CDJ under dry conditions (Fig. 1e).…”
Section: Collagen Fibers Are Continuous From Root Surface Through supporting
confidence: 68%
“…Nanomechanical tests on dry and wet specimens were performed using an AFM, to which a load-displacement transducer (Triboscope Micromechanical Test Instrument, Hysitron Incorporated, MN) was attached [8]. A sharp diamond Berkovich indenter with a radius of curvature less than 100 nm (Triboscope Micromechanical Test Instrument, Hysitron Incorporated, Minneapolis, MN) was fitted to the transducer.…”
Section: Atomic Force Microscopy and Afm-based Nanoindentation Of Ultmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have shown that enamel crystals are formed at a given distance from the dentine surface (Simmer and Fincham 1995;Diekwisch et al 1995;Aoba 1996;Bodier-Houllé et al 2000) and could either reach dentine crystals by a subsequent growth (Takano et al 1996) or remain distant (Bodier-Houllé et al 2000;Dong and Warshawsky 1996). In addition, there are both a cementum-enamel junction (CEJ) (Wang et al 2006b), which is quite similar to DEJ, and a cementumdentine junction (CDJ) (Ho et al 2004(Ho et al , 2005Jang et al 2014).…”
Section: Teethmentioning
confidence: 99%